Symmetric Cryptographic Protocols - Ramkumar, Mahalingam (Springer International Publishing : Imprint: Springer, 2014)
This book focuses on protocols and constructions that make good use of symmetric pseudo random functions (PRF) like block ciphers and hash functions - the building blocks for symmetric cryptography. Readers will benefit from detailed discussion of several strategies for utilizing symmetric PRFs. Coverage includes various key distribution strategies for unicast, broadcast and multicast security, and strategies for constructing efficient digests of dynamic databases using binary hash trees.   •        Provides detailed coverage of symmetric key protocols •        Describes various applications of symmetric building blocks •        Includes strategies for constructing compact and efficient digests of dynamic databases.